PENGARUH PENGALAMAN PENGGUNA DAN KUALITAS LAYANAN TERHADAP PENGINGATAN KEMBALI MEREK GRAB - Dharomesz, Vonezyo Yupanzara (Jurnal Manajemen, 2022)
This research aims to examine the impact of user experience and service quality on brand recall on Grab mobile apps. A total of 261 users of Grab mobile apps, were used as the sample based on criteria determined in the study such as gender, age by generation, occupation, and income. Hypothesis testing in this research is using logistic regression analysis techniques with SPSS. The results of the study found that the user experience of Grab mobile apps had a positive and significant impact on brand recall. Service quality influences brand recall of Grab on all four services. It can be mentioned that brand recall on online mobile application-based transportation services Grab is easier to recall for its users to use.